Faktor Maternal yang Berhubungan dengan Kejadian Sindrom HELLP pada Pasien Preeklamsia di RSUD Dr. H. Abdul Moeloek Bandar Lampung - Keyla Aisya Putri; Reni Zuraida; Selvi Marcellia; Efriyan Imantika (Medula, 2026)
HELLP syndrome (Hemolysis, Elevated Liver Enzymes, and Low Platelet Count) is a severe complication of preeclampsia that increases maternal and perinatal morbidity and mortality. Maternal factors such as age, parity, and nutritional status are thought to be associated with the occurrence of HELLP syndrome. This study aimed to analyze the association between maternal age, parity, and nutritional status and the incidence of HELLP syndrome among preeclamptic patients at Dr. H. Abdul Moeloek Regional General Hospital, Bandar Lampung. This analytic observational study used a case-control design based on medical records of preeclamptic patients from 2023 to 2025. The sample consisted of 50 respondents, comprising 25 preeclamptic patients with HELLP syndrome as cases and 25 preeclamptic patients without HELLP syndrome as controls, selected using purposive sampling according to inclusion and exclusion criteria. Data were analyzed using univariate and bivariate Chi-Square tests, with Odds Ratios (OR) and 95% confidence intervals (CI) calculated to assess the strength of association. The results showed significant associations between maternal age and HELLP syndrome (p=0.045; OR=3.27; 95% CI 1.01–10.62) and between nutritional status and HELLP syndrome (p<0.001; OR=51.00; 95% CI 5.82–446.56). No significant association was found between parity and HELLP syndrome (p=0.544; OR=1.45; 95% CI 0.44–4.78). In conclusion, maternal age and nutritional status were associated with HELLP syndrome among preeclamptic patients, whereas parity showed no significant association. Early identification of these maternal factors during the antenatal period is important to support early detection in high-risk pregnancies.